PECULIARITIES AND DEVELOPMENT STRATEGIES OF ARCHITECTURAL DECORATIVE ART IN THE ANCIENT HUIZHOU REGION, CHINA - XUE , MEI; BULHAKOVA, T. V. (Art and Design, 2024)
Purpose of this study is to conduct a comprehensive analysis of the ancient decorative art of Huizhou, identifying its aesthetic, symbolic, and technological characteristics, as well as exploring its development pathways in the modern era through the use of digital technologies. Methodology. This research employs iconography, literature analysis, comparative studies, and other methods to classify and theoretically summarize drawings and textual materials. Results. The study analyzes the reasons behind the establishment of decorative art in ancient Huizhou. It identifies the aesthetic and technological features of the decor in three primary types of traditional crafts in this region. Based on the analysis of ornaments, patterns, forms, their compositions, semantics, and manufacturing technologies, the decorative art of Huizhou is systematically categorized from the perspective of symbolic and cultural meaning, as well as technical methods and production tools. The social function, symbolism, and aesthetic value of Huizhou’s decorative art are revealed. Additionally, the prospects for developing and disseminating this ancient art through digital means are demonstrated. Scientific novelty. For the first time, Huizhou’s architectural decorative art has been systematically categorized from the perspectives of aesthetics, semantics, and technologies. Its unique artistic significance has been unveiled through a detailed analysis of compositions, their symbolic meaning, materials, and technological processes. A digitization and inheritance strategy for Huizhou’s "Three Carvings" (wood, stone, and brick) has also been formulated, aimed at protecting and promoting this intangible cultural heritage through modern scientific and technological means to realize the applied value of ancient art in contemporary design. Practical significance. The results of this study can be applied across various fields of art and design in the ancient Huizhou region by professionals such as digital artists, designers, engineers, and others, to create unique works and gain experience by integrating digital technologies with traditional decorative art.